From Verona, with love: “anti-gender” mobilizations and transfeminist (re)actions - Cossutta, Carlotta; Habed, Adriano José (My University, 2021)
In this article, we take Verona as an entry point to analyse “anti-gender” mobilizations in Italy and transfeminist reactions. We pro vide an overview of the Italian “anti-gender” campaign by describing the role of Catholic actors and the political Right. We therefore ex- amine the many forms these mobilizations have taken, especially between 2013 and 2017, and some of the responses by activists and academics during those years. We then consider some exemplary cases of both “anti- gender” attacks and transfeminist reactions that took place between 2018 and 2019. In particular, we focus on the so-called Pillon de- cree, which displays the link between “anti- gender” movements and legislative initiatives, on the Zelger motion against abortion presen- ted by the Verona City Council, and on the 13 th World Congress of Families that took place in Verona. We conclude with an exami- nation of the reactions to these events – the “Verona transfeminist city” demonstration and the creation of GIFTS, the Italian network of gender studies – in order to show the strength of the counterattack.
Keywords: Antifeminismus; Transgender; 300 Sozialwissenschaften; anti-gender; Rechte Bewegungen; Transfeminismus; Frauen- und LGBTQI+-Rechte